Plants and traditional knowledge: An ethnobotanical investigation on Monte Ortobene (Nuoro, Sardinia) - Bruschi Piero; Piredda Maddalena; Signorini Maria (BMC, 2009)
Abstract Background Most of the traditional knowledge about plants and their uses is fast disappearing as a consequence of socio-economic and land use changes. This trend is also occurring in areas that are historically exposed to very few external influences, such as Sardinia (Italy). From 2004 to 2005, an ethnobotanical investigation was carried out in the area of Monte Ortobene, a mountain located near Nuoro, in central Sardinia. Methods Data were collected by means of semi-structured interviews. All the records - defined as 'citations', i.e. a single use reported for a single botanical species by a single informant - were filed in a data base ('analytical table'), together with additional information: i.e. local names of plants, parts used, local frequencies, and habitats of plants, etc. In processing the data, plants and uses were grouped into general ('categories') and detailed ('secondary categories') typologies of use. Some synthetic indexes have also been used, such as Relative Frequency of Citation (RFC), Cultural Importance Index (CI), the Shannon-Wiener Index (H'), and Evenness Index (J). Results Seventy-two plants were cited by the informants as being traditionally used in the area. These 72 'ethnospecies' correspond to 99 botanical taxa (species or subspecies) belonging to 34 families. Three-hundred and one citations, 50 secondary categories of use, and 191 different uses were recorded, most of them concerning alimentary and medicinal plants. For the alimentary plants, 126 citations, 44 species, and 13 different uses were recorded, while for the medicinal plants, there were 106 citations, 40 species, and 12 uses. Few plants and uses were recorded for the remaining categories. Plants and uses for each category of use are discussed. Analyses of results include the relative abundance of botanical families, wild vs. cultivated species, habitats, frequency, parts of plant used, types of use, knowledge distribution, and the different cultural importance of the species in question. Conclusion The study provides examples of several interesting uses of plants in the community, which would seem to show that the custom of using wild plants is still alive in the Monte Ortobene area. However, many practices are no longer in use, and survive only as memories from the past in the minds of elderly people, and often only in one or just a few informants. This rapidly vanishing cultural diversity needs to be studied and documented before it disappears definitively.